Job Stress and Emotional Intelligence among Police Officer at General Operation Force, Royal Malaysia Police - Anuar Kamri, Khairol; Hafizuddin Mejah, Mohd; Abd Hamid, Aizathul Hani (International Journal of Psychosocial Rehabilitation, 2019)
Stress management and good emotional intelligence among police officers are crucial for the work environment that is always shifting from time to time. This article’s purpose of study is to identify the job stress and emotional intelligence level among police officers at the General Operation Force, Royal Malaysia Police. This study applied a quantitative approach through the fieldwork research method. The research instruments that have been used in this study are the questionnaire that was adapted from Schutte et al.’s (1998) entitled Emotional Intelligence and the job stress survey from McCreary & Thompsom’s (2006) as the key data collection instruments to address the research question and examine the conclusion of past literature reviews. The location of this study was conducted at the Battalion 6 PGA Bakri, Muar, Johor. By using the simple random sampling method, the sample size of this research is 196 respondents. Descriptive analysis of this research shows that stress levels are at a moderate level while emotional intelligence is at a high level. The implication of this study is that organizations need to emphasize intrinsic factors to employees, need to explain the role of employees in the organization, need to provide career development to employees, and management needs to have a positive relationship.